Billboards are they here to stay? a study of outdoor advertising signs in Guadalupe, EDSA Philippines - De los Reyes, Bernadette M. (College of Architecture, University of the Philippines Diliman, 2008)
The proliferation of billboards in our major thoroughfares has caused visual pollution. This calls for urgent need to describe the proper configuration of billboards in our streets. The study purports to formulate and advance a methodology to provide a systematic evaluation and measurement in determining its appropriateness in our streetscape. The amount of perceived complexity created by these elements thru its density, the number of repetition of information, its impact on the view from the road, and its arrangements formed according to street design, are the components measured for the evaluation. Specific approach of segmentation of street views was introduced. The result produced a poor to extremely poor quality effect of billboards in the Guadalupe streetview. The survey conducted yields almost the same result. Using visibility factor and other consideration, the study came up with a proposed billboard maximum size of 200sqm and a minimum spacing of 137 meters. This implies that a workable method is possible. Future studies using other factors can be studied to come up with a specific framework for this element.